(3YeOI GdEUdGM aj Yed UfGYI GdLQGMs - (3jYbhH Hf ESMGb GdeSjMj Gdedcj GdcQcj GHf Gdba, CHh GdaQL,J (B685 (3g` s
(3ChdgG (B:s
(3hHYO abO TcG Edi HYV LQGMi ReGffG bdI EgJeGe CQHGH gPG Gdaf HCeQ gPg GdUfGYI hGf hGMOkG efge de jYQa Shi JQcjH s
(3BNQgG (B:s
(3Ke ScQ fbi hRf QWdjf jOb hjVGa Edjg ChdG aChd , hjLYd aj TeS MGQI hjSJYed hGddg SHMGfg CYde s
(3fSNI QGHYIs
(3hjJNddgG ChQGb HNW MOjKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B161 ; (3eLdI GdeLeY GdYdei GdYQHi (B- (3GdLRA (B5 - (3U (B267 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLeYjI GdBSjhjI (B- (3cdcJG (B(332) s
Keywords: (3GdWHs